Modeling acute ischemic stroke recanalization through cyclic aspiration. (9th November 2021) - Oyekole, Oyekola; Simon, Scott; Manning, Keefe B.; Costanzo, Francesco
Abstract: We model the deformation of a thromboembolus lodged in a cerebral artery under the application of aspiration pressure as it would be provided by an aspiration catheter during a mechanical thrombectomy procedure. The system considered consists of (i) a clot modeled as a viscoelastic solid; (ii) an artery modeled as a hyperelastic solid; and (iii) a viscoelastic cohesive interface between the clot and the artery. For the chosen system and geometry, we show that the application of aspiration pressure results in the impingement of the thrombus against the inner arterial wall near the aspiration location. Conditions leading to interfacial failure are nucleated at the distal end of the clot and, depending on the details of the loading conditions, propagate toward the proximal end. The results provide useful information in identifying the circumstances that play a decisive role for clot removal by aspiration alone.